Punishment Learning in U.S. Veterans With Posttraumatic Stress Disorder. Issue 4 (26th July 2016) - Sawyer, Alice T.; Liverant, Gabrielle I.; Jun, Janie J.; Lee, Daniel J.; Cohen, Andrew L.; Dutra, Sunny J.; Pizzagalli, Diego A.; Sloan, Denise M.
Abstract: Learning processes have been implicated in the development and course of posttraumatic stress disorder (PTSD); however, little is currently known about punishment‐based learning in PTSD. The current study investigated impairments in punishment‐based learning in U.S. veterans. We expected that veterans with PTSD would demonstrate greater punishment‐based learning compared to a non‐PTSD control group. We compared a PTSD group with and without co‐occurring depression ( n = 27) to a control group (with and without trauma exposure) without PTSD or depression ( n = 29). Participants completed a computerized probabilistic punishment‐based learning task. Compared to the non‐PTSD control group, veterans with PTSD showed significantly greater punishment‐based learning. Specifically, there was a significant Block × Group interaction, F (1, 54) = 4.12, p = .047, η 2 = .07. Veterans with PTSD demonstrated greater change in response bias for responding toward a less frequently punished stimulus across blocks. The observed hypersensitivity to punishment in individuals with PTSD may contribute to avoidant responses that are not specific to trauma cues.